Thymidine kinase 2 and alanyl-tRNA synthetase 2 deficiencies cause lethal mitochondrial cardiomyopathy: case reports and review of the literature. (14th November 2016) - Mazurova, Stella; Magner, Martin; Kucerova-Vidrova, Vendula; Vondrackova, Alzbeta; Stranecky, Viktor; Pristoupilova, Anna; Zamecnik, Josef; Hansikova, Hana; Zeman, Jiri; Tesarova, Marketa; Honzik, Tomas
Abstract: Cardiomyopathy is a common manifestation in neonates and infants with mitochondrial disorders. In this study, we report two cases manifesting with fatal mitochondrial hypertrophic cardiomyopathy, which include the third known patient with thymidine kinase 2 deficiency and the ninth patient with alanyl-tRNA synthetase 2 deficiency. The girl with thymidine kinase 2 deficiency had hypertrophic cardiomyopathy together with regression of gross motor development at the age of 13 months. Neurological symptoms and cardiac involvement progressed into severe myopathy, psychomotor arrest, and cardiorespiratory failure at the age of 22 months. The imaging methods and autoptic studies proved that she suffered from unique findings of leucoencephalopathy, severe, mainly cerebellar neuronal degeneration, and hepatic steatosis. The girl with alanyl-tRNA synthetase 2 deficiency presented with cardiac failure and underlying hypertrophic cardiomyopathy within 12 hours of life and subsequently died at 9 weeks of age. Muscle biopsy analyses demonstrated respiratory chain complex I and IV deficiencies, and histological evaluation revealed massive mitochondrial accumulation and cytochrome c oxidase-negative fibres in both cases. Exome sequencing in the first case revealed compound heterozygozity for one novel c.209T>C and one previously published c.416C>T mutation in the TK2 gene, whereas in the second case homozygozity for the previously described mutation c.1774C>T in the AARS2 gene was determined. The thymidine kinase 2 mutations resulted in severe mitochondrial DNA depletion (to 12% of controls) in the muscle. We present, for the first time, severe leucoencephalopathy and hepatic steatosis in a patient with thymidine kinase 2 deficiency and the finding of a ragged red fibre-like image in the muscle biopsy in a patient with alanyl-tRNA synthetase 2 deficiency.